Factors influencing urban students to major in agriculture - Thielen, Sharon Leanne (Kansas State University, 2012)
Colleges of agriculture across the country are challenged to produce more graduates in order to meet the increase in employment opportunities in the areas of agriculture, food, and renewable natural resources. To attract students from areas with the most growth, urban communities, this study identified factors such as exposures to agriculture, college factors, and career aspirations that influenced urban students to major in agriculture and enroll in the College of Agriculture at Kansas State University (KSU). The accessible sample consisted of 125 students currently majoring in the College of Agriculture (agriculture students) and 18 students no longer majoring in the College of Agriculture (non-agriculture students) who completed the online questionnaire. Students from both groups were predominately female, non-minority students from the state of Kansas who entered KSU as incoming freshmen. The majors most represented were animal sciences and industry, pre-veterinary medicine, and food science and industry. The mean ACT score for agriculture students was 26.23 and 24.81 for non-agriculture students. For both groups of students, having a relative who worked in a field related to agriculture (grandparents, parent/guardian, aunt and uncle) was influential when they chose their academic major. A higher percentage of agriculture students had a relative who worked in a field related to agriculture or in production agriculture, compared to non-agriculture students. Career opportunities for graduates, hands-on-learning opportunities, friendly atmosphere in the College of Agriculture, visit to campus, quality and reputation of college faculty, availability of academic programs, and affordability of KSU were college factors most influential among the sample of students. Least influential factors were interaction with alumni, agriculture related camps and competitive events on campus, and ability to take online courses. Agriculture students were more influenced by career aspirations specific to career interests, such as working with people and animals, being able to use their creativity, or work with their hands. Non-agriculture students were influenced by broader career aspirations, such as having a job they enjoyed or being able to advance in their career.
Keywords: Career Aspirations; College Factors; Agriculture; Urban Students; Exposure to Agriculture; Agriculture, General (0473); Education, Agricultural (0517)